Correlation and path analysis in ginger (Zingiber officinale Rose.) - Latha, Z Abraham, M (Journal of Spices and Aromatic Crops, 2003)
Twelve morphological characters recorded from 40 genotypes of ginger were subjected to correlation and path analysis. The results revealed that all characters studied have positive correlation with yield and direct selection based on leaflet number, rhizome length and thickness of secondary rhizome could help to improve the yield. The lowest residual effect indicates the optiInistic nature of the characters taken for the study.